Plant Physiology Annual Volume 2023 (IntechOpen, 2024)
This book summarizes the design of drought-tolerant crops through CRISPR/Cas-mediated genome editing, focusing on reprogramming gene expression patterns that regulate the balance of plant hormones. The organic farming system is presented to highlight the potential role of alleviating changing climate-related abiotic stress. The current knowledge of artificial photosynthesis systems and cellular processes related to photosynthetic biochemistry was illustrated. Additionally, it explores intriguing subtopics of plant physiology, including an alternative natural rubber source and plant reproductive strategies, contributing to advancements in agricultural biotechnology. Recommended for students, teachers, and researchers interested in applied plant physiology, plant biochemistry, and crop breeding.